Prepreg, fiber-reinforced composite material, tubular body made of fiber-reinforced composite material, golf club shaft, and fishing rod
The prepreg composition, featuring a blend of specific epoxy resins and additives, addresses the challenges of mechanical properties, appearance, and tackiness in fiber-reinforced composite materials, resulting in enhanced performance for applications like golf shafts and fishing rods.
Patent Information
- Application Number
- JP2023503119
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-02-16
- Filing Date
- 2023-01-10
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-01-10
AI Technical Summary
Existing fiber-reinforced composite materials used in applications like golf shafts and fishing rods face challenges in achieving excellent mechanical properties, appearance, and tackiness simultaneously.
A prepreg composition containing a specific blend of epoxy resins, dicyandiamide, a compound with a high boiling point, and phenoxy resin, which when molded, produces a fiber-reinforced composite material with enhanced mechanical properties, appearance, and tackiness.
The resulting fiber-reinforced composite materials exhibit improved bending strength, elastic modulus, low coloring, transparency, weather resistance, and excellent tackiness, making them suitable for various applications including golf club shafts and fishing rods.
Smart Images

Figure 0007666581000001 
Figure 0007666581000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a prepreg, a fiber-reinforced composite material, and a tubular body made of a fiber-reinforced composite material that are suitable for use as fiber-reinforced composite materials for aerospace applications, general industrial applications, sports applications, and the like, and also to a golf club shaft and a fishing rod that use the tubular body made of the fiber-reinforced composite material. [Background technology]
[0002] Fiber-reinforced composite materials using carbon fibers, aramid fibers, or the like as reinforcing fibers are widely used, taking advantage of their high specific strength and specific elastic modulus, in structural materials for aircraft and automobiles, etc., sports materials such as tennis rackets, golf shafts, fishing rods, bicycles, and housings, general industrial applications, etc. As the resin composition used in these fiber-reinforced composite materials, thermosetting resins are mainly used from the viewpoints of heat resistance and productivity, and among them, epoxy resins are preferably used from the viewpoint of mechanical properties such as adhesion to reinforcing fibers.
[0003] In recent years, in order to apply fiber-reinforced composite materials to applications such as golf shafts, fishing rods, and bicycles, which require further weight reduction, improvements in various physical properties have been required. For example, prepregs used in tubular bodies such as golf shafts and fishing rods are required to have excellent tackiness in order to prevent the prepregs from peeling off when shaped into a tube. In addition, in order to achieve excellent bending strength in a tubular body, the fiber-reinforced composite material used needs to have high strength in the fiber direction and in the non-fiber direction, which are greatly influenced by the strength and elastic modulus of the epoxy resin itself used as the matrix resin. Furthermore, there are increasing cases in which the cross stitches of the reinforcing fibers are used as a design by clear coating the surface of the fiber-reinforced composite material. Therefore, in addition to the excellent mechanical properties of the cured product, importance has been attached to the appearance of the cured product, such as low colorability, transparency, and weather resistance.
[0004] In order to solve the above problems, from the viewpoint of improving mechanical properties, Patent Document 1 considers a method of improving resin strength by blending an additive to reduce the amount of dicyandiamide used as a curing agent that remains undissolved and causes defects. Also, from the viewpoint of improving appearance, Patent Document 2 considers a method of reducing the content of dicyandiamide, which is a factor that impairs the appearance of molded products, and obtaining a cured product by self-polymerization of epoxy resin. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2019 / 181402 [Patent Document 2] International Publication No. 2018 / 003691 Summary of the Invention [Problem to be solved by the invention]
[0006] When the technology of Patent Document 1 is used, the effect of improving the resin strength is obtained, but no consideration is given to appearance such as low colorability and weather resistance, and there are cases where an excellent appearance is not obtained. Furthermore, when the technology of Patent Document 2 is used, a resin cured product or molded product with an excellent appearance is obtained, but the bending strength and elastic modulus of the resin cured product are low, and the mechanical properties are insufficient. Furthermore, the technology of Patent Document 2 may lack the desired tack, and there is room for improvement in terms of handling.
[0007] Therefore, an object of the present invention is to provide a prepreg that is excellent in both mechanical properties such as strength and elastic modulus, and in appearance such as low colorability, transparency and weather resistance, and also has excellent tackiness, as well as a fiber-reinforced composite material, a tubular body made of a fiber-reinforced composite material, a golf club shaft, and a fishing rod that use the prepreg. [Means for solving the problem]
[0008] The present invention employs the following means to solve the above problems. That is, the prepreg of the present invention is a prepreg containing reinforcing fibers and a resin composition, The resin composition is a prepreg comprising the following components [A] to [D] and satisfying the following conditions (1) to (3). Component [A]: Epoxy resin Component [B]: Dicyandiamide Component [C]: A compound having a boiling point of 130° C. or higher and a molecular weight m of 50 to 250, which does not have an epoxy group in the molecule and does not substantially have the ability to harden epoxy resins. Component [D]: Phenoxy resin (1): As the component [A], [A1] an isocyanuric acid type epoxy resin is contained in an amount of 10 to 40 parts by mass per 100 parts by mass of the total epoxy resin. (2): The component [A] contains 10 to 50 parts by mass of a novolac-type epoxy resin [A2] relative to 100 parts by mass of the total epoxy resin. (3): The content of the glycidylamine-type epoxy resin [A3] as the component [A] is 10 parts by mass or less per 100 parts by mass of the total epoxy resin.
[0009] The fiber-reinforced composite material of the present invention is a fiber-reinforced composite material obtained by curing the above-mentioned prepreg.
[0010] The tubular body made of a fiber-reinforced composite material of the present invention is a tubular body made of a fiber-reinforced composite material obtained by molding the above-mentioned prepreg into a tubular shape.
[0011] The golf club shaft of the present invention is a golf club shaft formed using the above-mentioned tubular body made of a fiber-reinforced composite material.
[0012] The fishing rod of the present invention is a fishing rod comprising the above-mentioned tubular body made of a fiber-reinforced composite material. Effect of the Invention
[0013] According to the present invention, it is possible to obtain a prepreg which combines excellent mechanical properties and appearance and further has excellent tackiness, as well as a fiber-reinforced composite material, a tubular body made of a fiber-reinforced composite material, a golf club shaft, and a fishing rod which use the prepreg. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will be described in detail below.
[0015] The prepreg of the present invention includes a resin composition and reinforcing fibers. It is preferable that the prepreg is made of a resin composition and reinforcing fibers. An epoxy resin composition is used as the resin composition, and the prepreg includes components [A] to [D] as essential components. In the present invention, the term "component" refers to a resin or compound contained in the resin composition.
[0016] The component [A] in the present invention is an epoxy resin contained in the resin composition. When the component [A] is an epoxy resin having two or more epoxy groups in one molecule, the glass transition temperature of the cured product obtained by heat-curing the resin composition is high, and the heat resistance is high, which is preferable. An epoxy resin having one epoxy group in one molecule may be blended within a range that does not significantly adversely affect the heat resistance and mechanical properties of the epoxy resin composition or the fiber-reinforced composite material.
[0017] Examples of such epoxy resins include bisphenol type, isocyanuric acid type, phenol novolac type, cresol novolac type, dicyclopentadiene type, diaminodiphenylmethane type, diaminodiphenylsulfone type, aminophenol type, metaxylenediamine type, 1,3-bisaminomethylcyclohexane type, hydantoin type, sorbitol type, trishydroxyphenylmethane type, and tetraphenylolethane type epoxy resins.
[0018] In the present invention, in order to satisfy the condition (1), it is necessary to contain an isocyanuric acid type epoxy resin [A1] (hereinafter, sometimes simply referred to as [A1]) as the component [A]. By containing [A1], the flexural modulus of the cured resin is increased, the coloring of the cured resin is reduced, and the weather resistance is improved, resulting in a fiber-reinforced composite material with excellent mechanical properties and appearance.
[0019] It is necessary that the resin composition contains 10 to 40 parts by mass of [A1] relative to 100 parts by mass of the total epoxy resins contained in the resin composition, with the lower limit being preferably 15 parts by mass or more and the upper limit being preferably 30 parts by mass or less. By containing [A1] within this range, the resin cured product is less colored and cloudy, and has a good balance between the elastic modulus and the appearance (color, transparency).
[0020] Commercially available products of [A1] include "TEPIC (registered trademark)"-G, -S, -L, -VL, and -PAS B22 (all manufactured by Nissan Chemical Industries, Ltd.), and "Araldite (registered trademark)" PT9810 (manufactured by Huntsman Advanced Materials, Inc.).
[0021] In the present invention, in order to satisfy the condition (2), it is necessary to contain [A2] novolac type epoxy resin (hereinafter sometimes simply referred to as [A2]) as the component [A]. By containing [A2], the coloring of the resin cured product is reduced, the tackiness of the prepreg is improved, and a prepreg having excellent tackiness and a fiber reinforced composite material having excellent appearance can be obtained.
[0022] It is necessary to include 10 to 50 parts by mass of [A2] relative to 100 parts by mass of the total epoxy resins included in the resin composition, with the lower limit being preferably 15 parts by mass or more and the upper limit being preferably 40 parts by mass or less. By including [A2] within this range, the coloration and cloudiness of the cured resin are reduced, and the balance between the tackiness and the appearance (color and transparency) of the prepreg is good.
[0023] Examples of [A2] include phenol novolac epoxy resins and cresol novolac epoxy resins. Among them, as the phenol novolac epoxy resins and cresol novolac epoxy resins, those having a softening point of 60 to 110°C are preferably used, and those having a softening point of 70 to 100°C are more preferably used, because they have a good balance of physical properties such as tackiness when made into a prepreg.
[0024] Commercially available phenol novolac type epoxy resins include "jER (registered trademark)" 152, 154 (both manufactured by Mitsubishi Chemical Corporation), EPPN-201 (manufactured by Nippon Kayaku Co., Ltd.), "EPICLON (registered trademark)" N-740, N-770 (softening point: 65 to 75°C), N-775 (softening point: 70 to 80°C, all manufactured by DIC Corporation), and the like.
[0025] Commercially available cresol novolac epoxy resins include "EPICLON (registered trademark)" N-660 (softening point: 62 to 70°C), N-665 (softening point: 65 to 74°C), N-670 (softening point: 69 to 77°C), N-673 (softening point: 73 to 82°C), N-680 (softening point: 82 to 92°C), N-690 (softening point: 88 to 98°C), and N-695 (softening point: 90 to 100°C, all manufactured by DIC Corporation).
[0026] In order to satisfy the condition (3) in the present invention, the content of the glycidylamine type epoxy resin [A3] (hereinafter sometimes simply referred to as [A3]) as the component [A] must be 10 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably substantially free of [A3], relative to 100 parts by mass of the total epoxy resin. The glycidylamine type epoxy resin refers to an epoxy resin having a glycidylamino group, and by reducing the content of [A3] to 10 parts by mass or less, the resin cured product is less colored, the weather resistance is improved, and a fiber reinforced composite material having excellent appearance (color, weather resistance) can be obtained. Here, "substantially free of [A3]" means that the content of [A3] is less than 1 part by mass, including the case where the content of [A3] is zero, relative to 100 parts by mass of the total epoxy resin.
[0027] Examples of [A3] include diaminodiphenylmethane type epoxy resins, diaminodiphenylsulfone type epoxy resins, aminophenol type epoxy resins, metaxylenediamine type epoxy resins, and 1,3-bisaminomethylcyclohexane type epoxy resins.
[0028] Commercially available diaminodiphenylmethane epoxy resins include ELM434 (manufactured by Sumitomo Chemical Co., Ltd.), Araldite (registered trademark) MY720, MY721, MY9512, and MY9663 (all manufactured by Huntsman Advanced Materials, Inc.), Epotohto (registered trademark) YH-434 (manufactured by Nippon Steel Chemical & Material Co., Ltd.), and jER (registered trademark) 604 (manufactured by Mitsubishi Chemical Corporation).
[0029] Commercially available diaminodiphenylsulfone type epoxy resins include TG3DAS (manufactured by Mitsui Fine Chemicals, Inc.).
[0030] Commercially available aminophenol-type epoxy resins include ELM120 and ELM100 (both manufactured by Sumitomo Chemical Co., Ltd.), jER (registered trademark) 630 (manufactured by Mitsubishi Chemical Corporation), and Araldite (registered trademark) MY0500, MY0510, MY0600, and MY0610 (all manufactured by Huntsman Advanced Materials, Inc.).
[0031] An example of a commercially available meta-xylylenediamine type epoxy resin is "TETRAD (registered trademark)"-X (manufactured by Mitsubishi Gas Chemical Company, Inc.).
[0032] An example of a commercially available 1,3-bisaminomethylcyclohexane type epoxy resin is "TETRAD (registered trademark)"-C (manufactured by Mitsubishi Gas Chemical Company, Inc.).
[0033] Concerning the component [A], it is preferable to contain [A4] bisphenol type epoxy resin (hereinafter, sometimes simply referred to as [A4]). By containing [A4], the viscosity of the resin composition can be adjusted without impairing the color, transparency, and weather resistance of the resin cured product, and therefore the tack of the prepreg can be improved, and it is preferable to contain it in order to prepare a prepreg with excellent handleability.
[0034] [A4] includes bisphenol A type epoxy resin and bisphenol F type epoxy resin. The resin composition preferably contains 10 to 60 parts by mass of [A4] relative to 100 parts by mass of all epoxy resins contained in the resin composition, and more preferably the lower limit is 15 parts by mass or more and the upper limit is 50 parts by mass or less.
[0035] Commercially available bisphenol A type epoxy resins include jER (registered trademark) 825, 828, 834, 1001, 1002, 1003, 1003F, 1004, 1004AF, 1005F, 1006FS, 1007, 1009, and 1010 (all manufactured by Mitsubishi Chemical Corporation), EPICLON (registered trademark) 850 (manufactured by DIC Corporation), Epotohto (registered trademark) YD-128 (manufactured by Nippon Steel Chemical & Material Co., Ltd.), and DER-331 and 332 (all manufactured by The Dow Chemical Company).
[0036] Commercially available bisphenol F type epoxy resins include "Araldite (registered trademark)" GY282 (manufactured by Huntsman Advanced Materials, Inc.), "jER (registered trademark)" 806, 807, 4005P, 4007P, and 4010P (all manufactured by Mitsubishi Chemical Corporation), "EPICLON (registered trademark)" 830 (manufactured by DIC Corporation), and "Epotohto (registered trademark)" YD-170 (manufactured by Nippon Steel Chemical & Material Co., Ltd.).
[0037] In addition, for the component [A], the total amount of the isocyanuric acid type epoxy resin [A1], the novolac type epoxy resin [A2], and the bisphenol type epoxy resin [A4] is preferably 96% by mass or more, more preferably 99% by mass or more, and even more preferably 100% by mass of the total epoxy resins, so that the mechanical properties (strength, elastic modulus) and appearance (color, transparency, weather resistance) of the cured resin and the tackiness of the prepreg are excellent, which is preferable. In addition, the present invention does not prevent the component [A] from containing epoxy resins other than the above-mentioned [A1] to [A4], but the amount thereof is preferably less than 4% by mass when the amount of the total epoxy resins is taken as 100% by mass.
[0038] The component [B] in the present invention is dicyandiamide contained in the resin composition. Dicyandiamide is excellent in imparting high mechanical properties and heat resistance to the cured product of the epoxy resin, and is widely used as a curing agent for various epoxy resins. In addition, it is suitable for use because it provides excellent storage stability to the epoxy resin composition. Commercially available products of such dicyandiamide include DICY7 and DICY15 (both manufactured by Mitsubishi Chemical Corporation).
[0039] In the present invention, the content of component [B] is preferably 4 to 9 parts by mass, and more preferably 5 to 7 parts by mass, per 100 parts by mass of the total epoxy resin, because this provides an excellent balance between the mechanical properties and transparency of the cured resin.
[0040] The component [C] in the present invention is a compound contained in the resin composition, which has a boiling point of 130°C or more and a molecular weight m of 50 to 250, does not have an epoxy group in the molecule, and does not substantially have the ability to harden epoxy resins. Here, compounds such as amines and phenols capable of addition reaction with epoxy resins, acid anhydrides capable of copolymerizing with epoxy resins, imidazoles capable of being self-polymerization initiators for epoxy resins, aromatic urea compounds, and tertiary amine compounds are compounds that have the ability to harden epoxy resins. And, "substantially does not have the ability to harden epoxy resins" means that they do not chemically react with epoxy resins and are not involved in the self-polymerization of epoxy resins.
[0041] The component [C] is not incorporated into the crosslinked structure formed by the reaction of the epoxy resin with dicyandiamide, but exists in the voids, i.e., is included in the crosslinked structure, and is considered to maintain the state it had before the epoxy resin was cured without undergoing any chemical or physical changes even after the epoxy resin is cured, which is considered to increase the elastic modulus of the resulting epoxy resin cured product. Moreover, surprisingly, by blending the component [C], an epoxy resin cured product having not only a high elastic modulus but also high elongation and strength can be obtained.
[0042] In addition, by making the boiling point of the component [C] 130°C or higher, more preferably 180°C or higher, it is possible to suppress the volatilization of the component [C] when the epoxy resin composition is cured, and a resin cured product or a fiber-reinforced composite material having excellent mechanical properties can be obtained. In addition, by making the boiling point of the component [C] within this range, it is possible to suppress the generation of voids and the deterioration of mechanical properties in the obtained fiber-reinforced composite material, which is preferable. In addition, although there is no particular upper limit for the boiling point of the component [C], it is preferable to use a compound having a boiling point of 400°C or lower that is normally used in the present invention.
[0043] The content of the component [C] is preferably 1 to 15 parts by mass, more preferably 2 to 10 parts by mass, and further preferably 3 to 6 parts by mass, per 100 parts by mass of the component [A].
[0044] The molecular weight m of the component [C] is from 50 to 250, and more preferably from 70 to 120. By setting the molecular weight of the component [C] within this range, the component [C] is appropriately held in the voids of the crosslinked structure formed by the reaction of the epoxy resin with dicyandiamide, and a cured product excellent in elastic modulus, strength, and elongation can be obtained.
[0045] In the present invention, the component [C] is preferably a compound having at least one functional group selected from the group consisting of an amide group, a ketone group, and a hydroxyl group in the molecule. When the component [C] has such a highly polar functional group in the molecule, a strong intermolecular interaction occurs between the hydroxyl group in the crosslinked structure formed by the components [A] and [B] and the component [C], and the component [C] is easily held appropriately in the voids of the crosslinked structure, thereby obtaining a particularly excellent effect of improving elongation and strength.
[0046] Examples of such a component [C] include amides such as N-methylformamide, N-methylacetamide, 2-pyrrolidone, N-methylpropionamide, N-ethylacetamide, N-methylacetanilide, and N,N'-diphenylacetamide, and diols such as ethanediol, propanediol, butanediol, pentanediol, hexanediol, and heptanediol. These compounds may be used alone or in appropriate combination.
[0047] The component [D] in the present invention is a phenoxy resin contained in the resin composition. The phenoxy resin can improve the viscosity of the resin composition and the tackiness of the prepreg without impairing the color, transparency, and weather resistance of the resin cured product. Therefore, by containing the component [D], a prepreg having excellent tackiness and a fiber reinforced composite material having excellent appearance can be obtained. The component [D] is preferably contained in an amount of 3 to 20 parts by mass, more preferably 5 to 15 parts by mass, per 100 parts by mass of the component [A].
[0048] The resin composition used in the prepreg of the present invention may contain a curing accelerator from the viewpoint of controlling the curing rate. Examples of the curing accelerator include urea compounds and imidazole compounds, and from the viewpoint of the storage stability of the epoxy resin composition, urea compounds are particularly preferably used.
[0049] Examples of the urea compound include 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, phenyldimethylurea, toluenebisdimethylurea, etc. Commercially available aromatic urea compounds include DCMU99 (manufactured by Hodogaya Chemical Co., Ltd.) and "Omicure (registered trademark)" 24 (manufactured by PTI Japan Co., Ltd.).
[0050] The reinforcing fibers used in the prepreg and fiber-reinforced composite material of the present invention preferably include carbon fibers, graphite fibers, aramid fibers, glass fibers, etc., but it is particularly preferable to use carbon fibers. The form and arrangement of the reinforcing fibers are not limited, and for example, fiber structures such as long fibers aligned in one direction, single tows, woven fabrics, knits, and braids are used. As the reinforcing fibers, two or more types of carbon fibers, glass fibers, aramid fibers, boron fibers, polybenzoxazole fibers, high-strength polyethylene fibers, alumina fibers, silicon carbide fibers, etc. may be used in combination.
[0051] Specific examples of carbon fibers include acrylic, pitch and rayon carbon fibers, with acrylic carbon fibers having particularly high tensile strength being preferably used.
[0052] The carbon fiber can be in the form of twisted yarn, untwisted yarn, non-twisted yarn, etc., but in the case of twisted yarn, the filaments that make up the carbon fiber are not oriented parallel to one another, which can cause a decrease in the mechanical properties of the resulting carbon fiber reinforced composite material. Therefore, untwisted yarn or non-twisted yarn, which provide a good balance between the formability and strength properties of the carbon fiber reinforced composite material, are preferably used.
[0053] The tensile modulus of the carbon fiber is preferably in the range of 200 to 440 GPa. The tensile modulus of the carbon fiber is affected by the crystallinity of the graphite structure constituting the carbon fiber, and the higher the crystallinity, the higher the modulus. This range is preferable because the rigidity and strength of the carbon fiber reinforced composite material are all well balanced at a high level. The modulus of elasticity is more preferably in the range of 230 to 400 GPa, and even more preferably in the range of 260 to 370 GPa. Here, the tensile modulus of elasticity of the carbon fiber is a value measured according to JIS R7601 (2006).
[0054] The prepreg of the present invention can be produced by various known methods. For example, the prepreg can be produced by a hot melt method in which a resin composition is heated to reduce its viscosity without using an organic solvent and then impregnated into reinforcing fibers.
[0055] In the hot melt method, a resin composition whose viscosity has been reduced by heating can be directly impregnated into the reinforcing fibers, or a release paper sheet with a resin film is first prepared by coating the resin composition on release paper or the like, and then a resin film is placed on the reinforcing fiber side from both sides or one side of the reinforcing fibers, and the resin composition is impregnated into the reinforcing fibers by heating and pressurizing.
[0056] The content of reinforcing fibers in the prepreg is preferably 30 to 90% by mass, more preferably 35 to 85% by mass, and even more preferably 65 to 85% by mass, when the mass of the prepreg is taken as 100% by mass. If the content of reinforcing fibers is small, the amount of resin is too large, making it difficult to obtain the advantages of a fiber-reinforced composite material that is excellent in specific strength and specific modulus. In addition, when molding a fiber-reinforced composite material, the amount of heat generated during curing may become too high. On the other hand, if the content of reinforcing fibers is too large, impregnation of the resin may be insufficient, and the obtained composite material may have many voids. In addition, the tackiness of the prepreg may be impaired.
[0057] The fiber-reinforced composite material of the present invention or the tubular body made of a fiber-reinforced composite material can be produced, for example, by laminating the above-mentioned prepregs of the present invention in a predetermined shape and applying pressure and heat to harden the resin. Methods for applying heat and pressure include press molding, autoclave molding, bagging molding, wrapping tape method, internal pressure molding, etc.
[0058] The wrapping tape method is particularly preferably used as a method for forming a tubular body made of a fiber-reinforced composite material. The wrapping tape method is a method in which a prepreg is wound around a core metal such as a mandrel to obtain a cylindrical molded body. Specifically, the prepreg is wound around a mandrel, and a wrapping tape made of a thermoplastic resin film is wound around the outer periphery of the prepreg to fix and apply pressure to the prepreg. After the resin is heated and cured in an oven, the core metal is removed to obtain a cylindrical molded body. This method is suitable for producing rod-shaped bodies such as golf club shafts and fishing rods.
[0059] Since the tubular body made of a fiber-reinforced composite material of the present invention is formed by molding the prepreg having the above-mentioned excellent tackiness, peeling off when formed into a tubular shape is reduced, and a product with fewer defects such as voids can be obtained. Furthermore, when the prepreg according to the present invention is used, the cured product has excellent mechanical properties, so that the tubular body made of a fiber-reinforced composite material of the present invention exhibits excellent bending strength.
[0060] The fiber-reinforced composite material or the tubular body made of the fiber-reinforced composite material of the present invention can be widely used in aerospace applications, general industrial applications, and sports applications. More specifically, in general industrial applications, it is preferably used for structures such as automobiles, ships, and railway vehicles. In sports applications, it is preferably used for golf shafts, fishing rods, and tennis and badminton rackets. In particular, the tubular body made of the fiber-reinforced composite material of the present invention can be preferably used for golf club shafts and fishing rods.
[0061] The upper and lower limits of the numerical ranges described above can be combined in any combination unless otherwise specified. EXAMPLES
[0062] The present invention will be described in detail below with reference to examples. However, the present invention is not limited to these examples. The unit "parts" in the composition ratio means parts by mass unless otherwise noted. Furthermore, the measurements of various characteristics (physical properties) were performed in an environment with a temperature of 23°C and a relative humidity of 50% unless otherwise noted.
[0063] <Materials used in the Examples and Comparative Examples> (1) Component [A]: Epoxy resin · [A1] Isocyanuric acid type epoxy resin [A1]-1 "TEPIC (registered trademark)"-S (epoxy equivalent: 100, manufactured by Nissan Chemical Industries, Ltd.) [A2] Novolac type epoxy resin [A2]-1 "EPICLON (registered trademark)" N-775 (phenol novolac type epoxy resin, epoxy equivalent: 189, manufactured by DIC Corporation) [A2]-2 "EPICLON (registered trademark)" N-695 (cresol novolac type epoxy resin, epoxy equivalent: 214, manufactured by DIC Corporation) [A3] Glycidylamine epoxy resin [A3]-1 "Araldite (registered trademark)" MY0600 (aminophenol type epoxy resin, epoxy equivalent: 118, manufactured by Huntsman Advanced Materials, Inc.) [A3]-2 "Sumiepoxy (registered trademark)" ELM434 (diaminodiphenylmethane type epoxy resin, epoxy equivalent: 120, manufactured by Sumitomo Chemical Co., Ltd.) [A4] Bisphenol epoxy resin [A4]-1 "EPICLON (registered trademark)" 830 (bisphenol F type epoxy resin, epoxy equivalent: 172, manufactured by DIC Corporation) [A4]-2 "jER (registered trademark)" 4005P (bisphenol F type epoxy resin, epoxy equivalent: 1075, manufactured by Mitsubishi Chemical Corporation) (2) Component [B]: Dicyandiamide [B]-1 DICY7 (dicyandiamide, manufactured by Mitsubishi Chemical Corporation) (3) Component [C]: a compound having a boiling point of 130° C. or higher and a molecular weight m of 50 to 250, which does not have an epoxy group in the molecule and does not substantially have the ability to harden epoxy resins. [C]-1 1,2-propanediol (boiling point: 188°C, molecular weight m: 76, manufactured by Tokyo Chemical Industry Co., Ltd.) [C]-2 2-pyrrolidone (boiling point: 245°C, molecular weight m: 85, manufactured by Tokyo Chemical Industry Co., Ltd.) (4) Component [D]: Phenoxy resin [D]-1 "Fenotote (registered trademark)" YP-70 (manufactured by Nippon Steel Chemical & Material Co., Ltd.) (5) Other thermoplastic resins (hereinafter, component [E]) [E]-1 "Vinylec (registered trademark)" K (polyvinyl formal, manufactured by JNK Co., Ltd.) [E]-2 "Sumikaexcel (registered trademark)" PES 5003P (polyethersulfone, manufactured by Sumitomo Chemical Co., Ltd.) (6) Curing accelerator (hereinafter, component [F]) [F]-1 DCMU99 (3-(3,4-dichlorophenyl)-1,1-dimethylurea, manufactured by Hodogaya Chemical Co., Ltd.) (7) Carbon fiber "TORAYCA (registered trademark)" T1100G-24K (24,000 fibers, tensile modulus: 324GPa, manufactured by Toray Industries, Inc.) <Method for preparing epoxy resin composition> (1) Preparation of hardener master [A4]-1 was prepared in an amount of 10 parts by mass per 100 parts by mass of the total amount of epoxy resin. To this was added component [B]: dicyandiamide in the amount shown in the table, and kneaded at room temperature. The mixture was passed through a three-roll mill twice to prepare a hardener master.
[0064] (2) Preparation of epoxy resin composition Of the components and amounts shown in the table, the total amount of epoxy resin excluding the amount of [A4]-1 used in (1) above, that is, 90 parts by mass when the total amount of epoxy resin is 100 parts by mass, was put into a beaker. After heating to 150°C while kneading, the component [D] or component [E] with the components and amounts shown in the table was put in, and the mixture was heated and kneaded at a temperature of 150°C for 1 hour to dissolve. Next, the mixture was cooled to a temperature of 55 to 65°C while continuing the kneading, and then the hardener master prepared in (1) above, and the components [C] and [F] with the components and amounts shown in the table were put in, and kneaded at the same temperature for 30 minutes to obtain an epoxy resin composition.
[0065] <Method for producing cured epoxy resin> The epoxy resin composition prepared according to the above <Preparation method of epoxy resin composition> was degassed in a vacuum, and then in a mold set to a thickness of 2 mm using a 2 mm thick "Teflon (registered trademark)" spacer, the temperature was raised from 30°C at a rate of 1.7°C / min., and after reaching a temperature of 90°C, the temperature was maintained for 1 hour, and then the temperature was raised at a rate of 2.0°C / min., and after reaching a temperature of 135°C, the composition was cured for 2 hours to obtain a plate-shaped resin cured product having a thickness of 2 mm.
[0066] For appearance evaluation, the above curing reaction was carried out in a mold set to a thickness of 1 mm using a 1 mm Teflon (registered trademark) spacer, to obtain a 1 mm thick plate-like cured resin product.
[0067] <How to make prepreg> The epoxy resin composition prepared according to the above <Preparation method of epoxy resin composition> was applied onto a release paper using a knife coater to obtain a resin basis weight of 31 g / m 2 Next, two resin films with a fiber basis weight of 125 g / m were prepared. 2 The above resin film was laminated on both sides of the carbon fibers that were aligned in one direction to form a sheet, and the sheet was impregnated with the epoxy resin composition by heating and pressurizing at a temperature of 110°C and a maximum pressure of 2 MPa to obtain a prepreg.
[0068] <Various evaluation methods> (1) Three-point bending test of cured epoxy resin A test piece with a width of 10 mm and a length of 60 mm was cut out from the 2 mm thick cured resin product prepared according to the above <Preparation method of cured epoxy resin product>, and three-point bending was performed according to JIS K7171 (1994) using an Instron universal testing machine (manufactured by Instron Corp.) with a span of 32 mm, a crosshead speed of 2.5 mm / min, and sample number n=6. The arithmetic mean values of strength and elastic modulus were determined as the bending strength and bending elastic modulus of the cured resin product, respectively.
[0069] (2) Yellowness evaluation of cured epoxy resin A test piece 37 mm wide and 68 mm long was cut out from the 1 mm thick resin cured product prepared according to the above <Preparation method for epoxy resin cured product>. The tristimulus values of this test piece were determined by the reflection method using a multi-light source spectrophotometer MSC-P (manufactured by Suga Test Instruments Co., Ltd.) under optical conditions of D65 light source, 10° field of view, and d / 8 excluding specular reflection. The yellowness index was calculated according to JIS K7373 (2006) based on the obtained tristimulus values.
[0070] (3) Transparency evaluation of cured epoxy resin The 1mm thick cured resin product prepared according to the above <Preparation method of cured epoxy resin product> was placed on a piece of paper with writing on it to check the transparency of the cured resin product. If the writing was clearly readable, just like before the cured resin was placed on it, it was marked as A, if it was vague but still readable, it was marked as B, and if the writing was unreadable, it was marked as C.
[0071] (4) Weather resistance test of epoxy resin cured material A test piece 37 mm wide and 68 mm long was cut out from the 1 mm thick resin cured product prepared according to the above <Preparation method of epoxy resin cured product>. This test piece was subjected to an accelerated weather resistance test (Super Xenon Weather Meter SX-75, manufactured by Suga Test Instruments Co., Ltd.) to a strength of 180 W / m 2 The black panel temperature was 63°C, the humidity was 50% RH, and the irradiation time was 102 minutes without water injection and the intensity was 180 W / m 2A weather resistance test was conducted by repeating a cycle of 12 times (i.e., 24 hours) under conditions of a chamber temperature of 28°C and humidity of 99% RH, and 18 minutes of irradiation while spraying water.
[0072] Weather resistance was evaluated by measuring the color difference (ΔE) of the cured product before and after the weather resistance test using a multi-light source spectrophotometer MSC-P (manufactured by Suga Test Instruments Co., Ltd.). The tristimulus values (L * , a * , b * ) was calculated, and the difference in the tristimulus values before and after the weather resistance test (ΔL * , Δa * , Δb * ) was used to calculate the color difference (ΔE) according to the following formula (I).
[0073] ΔE={(ΔL * ) 2 +(Δa * ) 2 +(Δb * ) 2} 1 / 2 (I) (5) Measurement of tackiness of prepreg The tackiness of the prepreg was measured using a tack tester (PICMA Tack Tester II, manufactured by Toyo Seiki Co., Ltd.). A cover glass measuring 18 mm x 18 mm square was pressed onto the prepreg with a force of 0.4 kgf (3.9 N) for 5 seconds and pulled vertically at a speed of 30 mm / min. The resistance force at which the cover glass peeled off was taken as the tackiness value.
[0074] <Example 1> An epoxy resin composition was prepared according to the above <Preparation method of epoxy resin composition> using 25 parts by mass of "TEPIC (registered trademark)"-S as component [A1], 35 parts by mass of "EPICLON (registered trademark)" N-775 as component [A2], 25 parts by mass of "EPICLON (registered trademark)" 830 and 15 parts by mass of "jER (registered trademark)" 4005P as component [A4], 5.4 parts by mass of DICY7 as dicyandiamide, 5 parts by mass of 1,2-propanediol as component [C], 12 parts by mass of "Phenototo (registered trademark)" YP-70 as a phenoxy resin, and 3 parts by mass of DCMU99 as a curing accelerator.
[0075] From the obtained resin composition, a cured epoxy resin was produced according to the <Production method of cured epoxy resin>. The bending strength, bending modulus, yellowness index, transparency, and weather resistance (color difference ΔE) of this cured epoxy resin were measured, and the bending strength was 193 MPa, bending modulus was 4.7 GPa, yellowness index was 12, transparency was A, and ΔE was 6.8, indicating that the physical properties and appearance of the cured resin were good.
[0076] Furthermore, a prepreg was produced from the obtained resin composition according to the <Preparation Method for Prepreg>, and the tackiness of the prepreg was measured. The prepreg tackiness was 1.7 kgf, which showed excellent tackiness.
[0077] <Examples 2 to 12> Cured epoxy resin products and prepregs were produced in the same manner as in Example 1, except that the resin compositions were changed as shown in Table 1. The flexural strength, flexural modulus, yellowness index, transparency, weather resistance (color difference ΔE), and prepreg tack of the cured epoxy resin products of each Example were as shown in Table 1, and all were good.
[0078] <Comparative Example 1> Except for changing the resin composition as shown in Table 1, an epoxy resin cured product and a prepreg were produced in the same manner as in Example 1. The results of evaluating the physical properties are also shown in Table 1 (the same applies to the subsequent Comparative Examples). The yellowness index, transparency, weather resistance, and prepreg tack of the epoxy resin cured product were good. However, the content of [A1] per 100 parts by mass of the total epoxy resin was less than 10 parts by mass, which did not satisfy condition (1), and therefore the bending strength and bending modulus of the epoxy resin cured product were lower than those of Example 7.
[0079] <Comparative Example 2> Except for changing the resin composition as shown in Table 1, an epoxy resin cured product and a prepreg were produced in the same manner as in Example 1. The flexural modulus, yellowness index, weather resistance, and prepreg tack of the epoxy resin cured product were good. However, the content of [A1] exceeded 40 parts by mass per 100 parts by mass of the total epoxy resin, which did not satisfy condition (1), and therefore the flexural strength and transparency of the epoxy resin cured product were poorer than those of Example 6.
[0080] <Comparative Example 3> A cured epoxy resin product and a prepreg were produced in the same manner as in Example 1, except that the resin composition was changed as shown in Table 1. The cured epoxy resin product had good flexural modulus, yellowness index, transparency, and weather resistance. However, the content of [A2] per 100 parts by mass of the total epoxy resin was less than 10 parts by mass, which did not satisfy condition (2), and therefore the flexural strength and prepreg tack were lower than those of Example 7.
[0081] <Comparative Example 4> Except for changing the resin composition as shown in Table 1, an epoxy resin cured product and a prepreg were produced in the same manner as in Example 1. The flexural modulus, yellowness index, weather resistance, and prepreg tack of the epoxy resin cured product were good. However, since the content of [A2] exceeded 50 parts by mass per 100 parts by mass of the total epoxy resin, which did not satisfy condition (2), the flexural strength and transparency of the epoxy resin cured product were poorer than those of Example 4.
[0082] <Comparative Example 5> A cured epoxy resin material and a prepreg were produced in the same manner as in Example 1, except that the resin composition was changed as shown in Table 1. The cured epoxy resin material had good yellowness index, transparency, weather resistance, and prepreg tack. However, since component [B] was not included, the flexural strength and flexural modulus of the cured epoxy resin material were lower than those of Examples 5 and 9.
[0083] <Comparative Example 6> A cured epoxy resin material and a prepreg were produced in the same manner as in Example 1, except that the resin composition was changed as shown in Table 1. The cured epoxy resin material had good yellowness index, transparency, weather resistance, and prepreg tack. However, since component [C] was not blended, the flexural strength and flexural modulus of the cured epoxy resin material were lower than those of Example 5.
[0084] <Comparative Example 7> Except for changing the resin composition as shown in Table 1, an epoxy resin cured product and a prepreg were produced in the same manner as in Example 1. The flexural strength, flexural modulus, and prepreg tack of the epoxy resin cured product were good. However, because component [D] was not included and "Vinylec (registered trademark)" K was used instead as a thermoplastic resin, the yellowness, transparency, and weather resistance of the resin cured product were poorer than those of Example 1.
[0085] <Comparative Example 8> Except for changing the resin composition as shown in Table 1, an epoxy resin cured product and a prepreg were produced in the same manner as in Example 1. The bending strength, bending modulus, transparency, and prepreg tack of the epoxy resin cured product were good. However, since the content of [A3] exceeded 10 parts by mass per 100 parts by mass of the total epoxy resin, and condition (3) was not satisfied, the yellowness index and weather resistance of the resin cured product were poorer than those of Examples 1 and 8.
[0086] <Comparative Example 9> Except for changing the resin composition as shown in Table 1, an epoxy resin cured product and a prepreg were produced in the same manner as in Example 1. The bending strength, bending modulus, transparency, and prepreg tack of the epoxy resin cured product were good. However, since the content of [A3] exceeded 10 parts by mass per 100 parts by mass of the total epoxy resin, and condition (3) was not satisfied, the yellowness index and weather resistance of the resin cured product were poorer than those of Examples 1 and 8.
[0087] <Comparative Example 10> Except for changing the resin composition as shown in Table 1, an epoxy resin cured product and a prepreg were produced in the same manner as in Example 1. The flexural strength, flexural modulus, yellowness index, transparency, and prepreg tack of the epoxy resin cured product were good. However, since component [D] was not blended and "SumikaExcel (registered trademark)" PES 5003P was used instead as a thermoplastic resin, the weather resistance of the resin cured product was poorer than that of Example 1.
[0088] [Table 1-1]
[0089] [Table 1-2]
Claims
1. A prepreg comprising reinforcing fibers and a resin composition, The resin composition comprises the following components [A] to [D] and satisfies the following conditions (1) to (3): Component [A]: Epoxy resin Component [B]: Dicyandiamide Component [C]: a compound having a boiling point of 130° C. or higher and a molecular weight m of 50 to 250, which does not have an epoxy group in the molecule and does not substantially have the ability to harden epoxy resins. Component [D]: Phenoxy resin (1): The component [A] contains an isocyanuric acid type epoxy resin [A1] in an amount of 10 to 40 parts by mass per 100 parts by mass of the total epoxy resin. (2): The component [A] contains 10 to 50 parts by mass of [A2] a novolac-type epoxy resin per 100 parts by mass of the total epoxy resin. (3): The content of the glycidylamine-type epoxy resin [A3] as the component [A] is 10 parts by mass or less per 100 parts by mass of the total epoxy resin.
2. The prepreg according to claim 1, which is substantially free of the glycidyl amine-type epoxy resin [A3].
3. The prepreg according to claim 1 or 2, wherein the content of the component [B] is 4 to 9 parts by mass per 100 parts by mass of the total epoxy resins.
4. 3. The prepreg according to claim 1 or 2, comprising [A4] a bisphenol-type epoxy resin as the component [A].
5. A fiber-reinforced composite material obtained by curing the prepreg according to claim 1 or 2.
6. A tubular body made of a fiber-reinforced composite material, which is obtained by molding the prepreg according to claim 1 or 2 into a tubular shape.
7. A golf club shaft comprising the tubular body made of the fiber-reinforced composite material according to claim 6.
8. A fishing rod comprising the tubular body made of the fiber-reinforced composite material according to claim 6.
Citation Information
Patent Citations
Epoxy resin composition, adhesive film and pre-preg thereby, multilayer printed circuit board using same and its producing method
JP2001181375A
Flame-retardant carbon fiber reinforced composite
JP2007291227A
Epoxy resin composition, and film, prepreg and fiber-reinforced plastic using the same
JP2017226745A
Epoxy resin composition, prepreg, and fiber-reinforced composite material
WO2018003691A1
Prepreg and fiber-reinforced composite material
WO2019181402A1